Determination of Anatomical Variation of Mental Foramen and Evaluation of Anterior Loop in Karachi Population Using CBCT - Shaharyar Hamid Shaikh, Anwar Ali, Daud Sultan, Syeda Noureen Iqbal, M. lyas Shaikh, Saher Shaikh, Rehmatullah Kandhro, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the anatomical variation in mental foramen and to evaluate the anterior loop in the population of Karachi with the use of cone beam computed tomography (CBCT). Study Design: Prospective Study Place and duration: Department of Dental and Maxillofacial Surgery, Dr. Ishrat-ul-Ibad Khan Institute of Oral Health and Sciences Dow University of Health Sciences Karachi during September 2021 and February 2022. Methodology: A group of 160 subjects were included in this study and the simple convenient sampling technique was used to obtain data for the research. CBCT images of all patients were obtained. Results: 160 CBCT scans were obtained for this study, 76 females and the remaining 84 were males. Mental foramen was present below the second premolar and between the first and the second premolars most commonly, respectively. On the right side the mental foramen was 67.5% and 68.1% on the left. The most common shape of the anterior loop was Type-I, where Anterior Loop (AL) is unnoticeable and the anatomy is Y shaped as classified by solar et al. The AL was present more commonly on the left side 65% compared to the right side which was 59.4%. No correlation was found between anterior loop presentation and incisive canal of the mandibular region according to the Shapiro Wilk normality test (P≥0.05). Conclusion: It is evident in this study that the location of the anterior loop and mental foramen is variable in our study population. Therefore it is mandated that CBCT images should be used before any invasive procedure is undertaken in the MF region. Keywords: Anatomical variation, Mental foramen, Anterior loop, Mental Nerve, Cone Beam Computed Tomography (CBCT).